PENGARUH DISIPLIN TERHADAP KINERJA APARAT DESA SE-KECAMATAN KAIDIPANG KABUPATEN BOLAANG MONGONDOW UTARA - Nesa Putri Hente; Melizubaida Mahmud; Risca Marsanti Halid; Roy Hasiru; Sudirman Sudirman (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to examine and analyze the effect of work discipline on the performance of village officials in Kaidipang District, North Bolaang Mongondow Regency. Work discipline is considered an important factor that influences the performance of public officials in carrying out their duties and responsibilities in providing public services at the village level. This research employed a quantitative approach using a survey method. The population of this study consisted of all village officials in Kaidipang District, with a total sample of 35 respondents selected through a saturated sampling technique. Data were collected by distributing questionnaires developed based on indicators of work discipline and village officials’ performance. The collected data were then analyzed using simple linear regression to determine the relationship and influence between the research variables. The results of the analysis indicate that work discipline has a positive and significant effect on the performance of village officials in Kaidipang District, North Bolaang Mongondow Regency. This finding is supported by the correlation coefficient (R), which indicates a strong relationship between the variables. Furthermore, the coefficient of determination (R²) of 57.9 percent demonstrates that variations in village officials’ performance can be explained by work discipline, while the remaining percentage is influenced by other factors not included in this research model. Therefore, the hypothesis stating that work discipline has a positive effect on the performance of village officials is accepted.